Evolutionary selection of alleles in the melanophilin gene that impacts on prostate organ function and cancer risk. Issue 1 (14th September 2021) - Ermini, Luca; Francis, Jeffrey C; Rosa, Gabriel S; Rose, Alexandra J; Ning, Jian; Greaves, Mel; Swain, Amanda
Abstract: Background and objectives: Several hundred inherited genetic variants or SNPs that alter the risk of cancer have been identified through genome-wide association studies. In populations of European ancestry, these variants are mostly present at relatively high frequencies. To gain insight into evolutionary origins, we screened a series of genes and SNPs linked to breast or prostate cancer for signatures of historical positive selection. Methodology: We took advantage of the availability of the 1000 genome data and we performed genomic scans for positive selection in five different Caucasian populations as well as one African reference population. We then used prostate organoid cultures to provide a possible functional explanation for the interplay between the action of evolutionary forces and the disease risk association. Results: Variants in only one gene showed genomic signatures of positive, evolutionary selection within Caucasian populations melanophilin ( MLPH ). Functional depletion of MLPH in prostate organoids, by CRISPR/Cas9 mutation, impacted lineage commitment of progenitor cells promoting luminal versus basal cell differentiation and on resistance to androgen deprivation. Conclusions and implications: The MLPH variants influencing prostate cancer risk may have been historically selected for their adaptive benefit on skin pigmentation but MLPH is highly expressed in the prostate and the derivative, positively selected, alleles decrease the risk of prostate cancer. Our study suggests a potential functional mechanism via which MLPH and its genetic variants could influence risk of prostate cancer, as a serendipitous consequence of prior evolutionary benefits to another tissue. Lay Summary: We screened a limited series of genomic variants associated with breast and prostate cancer risk for signatures of historical positive selection. Variants within the melanophilin ( MLPH ) gene fell into this category. Depletion of MLPH in prostate organoid cultures, suggested a potential functional mechanism for impacting on cancer risk, as a serendipitous consequence of prior evolutionary benefits to another tissue.